Menu Naming as a Branding Strategy of Indonesian Restaurants in Kuala Lumpur: a Socio-onomastic Approach - Sya’adah, Himatus; Efendi, Agik Nur; Purnomo, Eko; Amirah, Syarifah Nur (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to identify strategic language components in Indonesian menu items and restaurants as part of a broader branding strategy for Indonesian establishments in Kuala Lumpur. Employing a qualitative approach based on Miles and Hubermanâ€™s interactive model alongside descriptive methods, the study ensures a thorough and systematic analysis. The primary data comprise menu listings from two selected restaurants, categorized into: (1) Indonesian restaurants offering a diverse range of dishes and (2) Indonesian franchise restaurants featuring a single branded menu. Data were also enriched through direct observation of both establishments. Findings from D’Chowkit Restaurant (R1) reveal that many menu items adopt unique and attention-grabbing names that reference cultural symbols and social conditions, thus associating the food with meanings beyond its culinary function. In contrast, Ayam Gepuk Pak Gembus (R2) exhibits minimal linguistic variation, relying instead on an already well-established brand image known for its reputation, quality, and prestige in both Indonesia and Malaysia. The brandâ€™s recognition alone strongly influences consumer perception. These findings demonstrate that linguistic choices in menu presentation, together with established brand narratives, not only attract consumer interest but also communicate cultural authenticity, create symbolic value, and reinforce Indonesiaâ€™s culinary identity within an increasingly competitive transnational context.